Design and Performance Investigation of a Carbon‐Free Pt/Ti Cathode with Low Membrane Degradation Rate for Proton Exchange Membrane Water Electrolyser. Issue 5 (10th April 2019) - Shi, Yan; Guo, Lili; Lu, Zhuoxin; Wang, Zhida; Gan, Yuan; Guo, Changqing; Tan, Hongyi; Yan, Changfeng
Abstract : In a proton exchange membrane (PEM) water electrolyser, Pt‐coated porous titanium plate always acts as the current collector both in the anode and cathode. However, the Pt particles on the Ti current collector cannot take part in the electrochemical reactions and thus lead to a lower utilization of the noble metal. In this work, the Pt‐coated Ti current collector is directly used as the cathode in the PEM water electrolyser instead of the conventional Pt/C electrode. To improve the performance, Nafion ionomer is coated on the Pt/Ti electrode to enlarge the electrochemical surface area (ECSA); the ECSA of the Pt/Ti electrode is increased by six times, and the utilization of Pt can be elevated to 45%. The voltage of the electrolyser with the Pt/Ti electrode is only 31 mV higher than the conventional Pt/C catalyst layer at 1 A cm −2 . After stability tests, an obvious membrane thinning is observed using Pt/C as the cathode while the membrane of the electrolyser with the ionomer‐coated Pt/Ti cathode does not show a significant change in thickness. The F ion emission rate shows the membrane degradation rate is reduced by 15 times compared with the conventional Pt/C cathode. Abstract : A current collector can act as an electrode. A Pt‐coated Ti current collector is used as the cathode of a proton exchange membrane water electrolyser instead of conventional Pt/C. The structure of the electrolyser is simplified, and the efficiency reaches above 85%. The membrane degradation rate is also reduced by 15 times, and the new cathode exhibits a positive impact on the membrane stability.